Design and Validation of an Ethical AI Micro-Credential for Pre-Service Teachers - Wiwik Indrayeni; Satria Efandi (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
The rapid expansion of generative artificial intelligence (AI) has increased the urgency of preparing future teachers to use AI responsibly. Teacher education has recognized the importance of digital competence, yet structured preparation for ethical AI use remains limited. This study aims to design and validate an Ethical AI Micro-Credential for pre-service teachers as a human-centered framework for strengthening ethical AI competence in teacher education. This study employed a Research and Development approach using the ADDIE model: analysis, design, development, implementation, and evaluation. Conducted at Universitas Negeri Padang, the study involved 150 pre-service teachers and three expert validators in curriculum, AI/educational technology, and educational psychology. Data were collected through curriculum analysis, expert validation sheets, pre-test and post-test instruments, observation, and a usability questionnaire based on the System Usability Scale. Quantitative data were analyzed using Aiken’s V, descriptive statistics, and paired-sample t-test, while qualitative feedback was analyzed descriptively. The results showed that the developed micro-credential achieved acceptable content validity, practical usability, and positive instructional relevance. The framework integrates six competency domains and improved participants’ understanding of ethical AI. The study concludes that the proposed micro-credential provides a validated and flexible model for embedding ethical AI competence into pre-service teacher education.